The Relationship between the Intensity of Worship and the Personality of Elementary School Teachers - Wildan Murtadho; Raden Fadli Daulay; Siti Nurhalizah; Riki Irawan; Mardianto Mardianto; Haidir Haidir (Universitas Pahlawan Tuanku Tambusai, 2023)
The personality of the teacher is the main focus in the digital era, because students can imitate the teacher's behavior in the real world and in cyberspace. This research examines the practice of daily worship, personality competence and the intensity of daily worship of IT TQ Miftahul Jannah Medan Private Elementary School educators. It is intended to identify the relationship between individual abilities. Gianna Medan. This type of research is quantitative research using correlation methods. The sampling technique is total sampling. This research was conducted at SD IT TQ Miftahul Jannah Medan. The population and sample of this study were all 16 educators. The data collection methodology of this study uses worship formats and questionnaires, and is tested for validity and reliability using IBM SPSS 27. Contribution and R-squared to determine the contribution of variable X to variable Y. The results of this study indicate that there is a correlation value of 0.936 between the intensity of daily worship with the personal performance of educators. This means that the magnitude of the relationship between the intensity of daily worship and the personal competence of educators is classified as very strong. This strengthens the results of the descriptive analysis of data for the intensity of daily worship in the moderate category of 44% and the personality competence of educators in the high category of 56%. The relationship between the practice of daily worship (X) and the personal performance of educators (Y) is 87.6%. Thus it is concluded that there is a significant relationship between the practice of worship, personality competence and the intensity of educators' worship at the basic education level.